Chapter Episcopal authority and networks in Carolingian times: recent approaches and perspectives - De Angelis, Gianmarco (Reti Medievali E-Book, 2022)
This paper introduces the volume, aiming first of all at presenting the historiographical framework in which the collected essays are placed and the common questions around which they revolve, with particular regard to typologies, characteristics, extension of the social and cultural networks that the Italian bishops built around themselves, and to their effects on the integration of the regnum in the Carolingian political structures.